Scapular Osteochondroma: A Unique Site in 50 Years Old: An Unusual Case - Ravi Sauhta; Dheeraj Makkar (Journal of Orthopedics, Traumatology and Rehabilitation)
Osteochondromas are benign bone tumors that mainly affect the metaphysis of long bones. We describe a 50-year-old patient who presented with a ventral scapular osteochondroma that limited her shoulder movement and induced paresthesia during sleep. The swelling was accompanied by pain and an inability to execute her professional obligations for the preceding 4 months. There were no neurological abnormalities. Computed tomography scan revealed a mushroom-shaped mass with cortical and medullary components near the scapula’s lateral angle. We carried out the surgery using the lateral decubitus position, general anesthesia, and the axillary approach. We describe a unique location and age range in which osteochondroma manifests. Because the risk of malignancy grows with age, we underline that osteochondroma should be considered a differential diagnosis in both unusual locations and age groups. Second, patients should be monitored clinically and radiographically following excision.